2012
DOI: 10.1155/2012/614196
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Tai-Chi Training and Detraining on Functional Capacity, Symptomatology and Psychological Outcomes in Women with Fibromyalgia

Abstract: Background. The purpose was to analyze the effects of Tai-Chi training in women with fibromyalgia (FM).Methods. Thirty-two women with FM (mean age, years) attended to Tai-Chi intervention 3 sessions weekly for 28 weeks. The outcome measures were: tenderness, body composition, functional capacity and psychological outcomes (Fibromyalgia impact questionnaire (FIQ), Short Form Health Survey 36 (SF-36)).Results. Patients showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 41 publications
3
35
0
1
Order By: Relevance
“…In a recent study, Romero-Zurita and colleagues [85] reported the effects of Tai Chi training in women with fibromyalgia. Thirty-two women with fibromyalgia attended Tai Chi intervention 3 sessions weekly for 28 weeks.…”
Section: Tai Chi For Rheumatological Diseasementioning
confidence: 99%
“…In a recent study, Romero-Zurita and colleagues [85] reported the effects of Tai Chi training in women with fibromyalgia. Thirty-two women with fibromyalgia attended Tai Chi intervention 3 sessions weekly for 28 weeks.…”
Section: Tai Chi For Rheumatological Diseasementioning
confidence: 99%
“…Others have shown no difference between Tai Chi groups and control groups [33,34]. In addition, most of the studies focus on only one ailment [32,35,36]. As far as we know, the majority of the literature on Tai Chi intervention for fatigue is empirical, and uses small sample sizes.…”
Section: Introductionmentioning
confidence: 99%
“…33 After 28 weeks of t'ai chi training, 3 times per week, 32 women with fibromyalgia had improvements on measures of pain, functional capacity, symptomology (e.g., number of tender points, fatigue), and psychologic outcomes. 34 Another study of patients with fibromyalgia (N = 36) found that 24 weeks-but not 12 weeks-of participation in a t'ai chi program reduced levels of acute pain. 35 Twelve breast-cancer survivors with associated myalgias (musculoskeletal pain) and arthalgias (joint pain), who participated in a t'ai chi program for 8 weeks, reported reduced stress, increased relaxation, and enhanced sleep quality.…”
Section: Musculoskeletal Conditionsmentioning
confidence: 99%